[Student selecting food at self-serve facility] (1965)
Male student selects a donut from a self-serve counter at an on-campus dining facility. The menu pictured in the upper left corner of the image states that the facility also offered "FRENCH FRIES, FRIED SHRIMP, GRILLED CHEESE [and] HAM SANDWICH"